2006
DOI: 10.4049/jimmunol.177.7.4252
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: ASC Mediates the Induction of Multiple Cytokines by Porphyromonas gingivalis via Caspase-1-Dependent and -Independent Pathways

Abstract: Porphyromonas gingivalis (Pg) is a major etiologic agent for chronic periodontitis. Tissue destruction by Pg results partly from induction of host inflammatory responses through TLR2 signaling. This work examines the role of apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC), an adaptor molecule important for TLR-mediated caspase-1 activation. Results demonstrate that ASC levels are stable upon infection of human THP1 monocytic cells with Pg but decrease after cytokine induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(117 citation statements)
references
References 24 publications
10
107
0
Order By: Relevance
“…Interestingly, the expression of the adaptor molecule ASC, that mediates NLR binding to Caspase-1, is down-regulated by A. actinomycetemcomitans infection. These results are in agreement with the up-regulation of NLRP3 [26] and down-regulation of ASC [26,54] in myelomonocytic Monomac-6 or monocytic THP1 cells, by the major periodontal pathogen Porphyromonas gingivalis. Similar findings were are also demonstrated in another experimental system, in which Listeria monocytogenes is shown to up-regulate NLRP3, but down-regulate NLRP6 and ASC expression in human peripheral blood mononuclear cells [55].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the expression of the adaptor molecule ASC, that mediates NLR binding to Caspase-1, is down-regulated by A. actinomycetemcomitans infection. These results are in agreement with the up-regulation of NLRP3 [26] and down-regulation of ASC [26,54] in myelomonocytic Monomac-6 or monocytic THP1 cells, by the major periodontal pathogen Porphyromonas gingivalis. Similar findings were are also demonstrated in another experimental system, in which Listeria monocytogenes is shown to up-regulate NLRP3, but down-regulate NLRP6 and ASC expression in human peripheral blood mononuclear cells [55].…”
Section: Discussionsupporting
confidence: 89%
“…ASC is reported to be required for the induction not only of IL-1β, IL-18, but also of IL-6, IL-8, IL-10, and TNF through both caspase-1-dependent and -independent mechanisms [25].…”
Section: Discussionmentioning
confidence: 99%
“…ShASC#1, shASC#2, and shASC#1mut THP1 cell lines were generated using retroviral vectors and have been characterized previously (18,23). DUSP10-expressing THP1 cells were generated using the full-length open reading frame cloned into lentiviral vector pLex-JRed (catalogue #OHS4493-98905681; Open Biosystems).…”
Section: Generation Of Cell Lines Isolation Of Mouse Macrophagesmentioning
confidence: 99%
“…Although periodontal disease is localized to the tissues surrounding the tooth, Pg infection predisposes people to more serious systemic conditions such as cardiovascular disease and delivery of preterm infants (29,31,32). Recently, we showed that, during Pg infection, ASC exhibits inflammasome-independent functions, including TNF-␣ and NF-B activation (23). We therefore elected to use this pathogen to reveal new ASC functions that might be separable from that of the inflammasome.…”
mentioning
confidence: 99%
See 1 more Smart Citation